Ontogeny of Hypothalamus-Pituitary Gonadal Axis and Minipuberty: An Ongoing Debate? - Bizzarri, Carla; Cappa, Marco (Frontiers in Endocrinology, 2020)
The fetal hypothalamus-pituitary gonadal (HPG) axis begins to function during mid-gestation but its activity decreases during late pregnancy due to the suppressive effects of placental estrogens. Placental hormones drop immediately after birth, FSH and LH surge at around 1 week and peak between 1 and 3 months of life. The HPG axis is activated in both sexes, but a sexual dimorphism is evident with higher LH values in boys, while FSH prevails in girls. Both gonadotrophins decline in boys by around 6 months of age. In girls, LH declines at the same time as in boys, while FSH persists elevated up to 3 or 4 years of age. As a result of gonadotropin activation, testicular testosterone increases in males and ovarian estradiol rises in females. These events clinically translate into testicular and penile growth in boys, enlargement of uterus and breasts in girls. The functional impact of HPG axis activity in infancy on later reproductive function is uncertain. According to the perinatal programming theory, this period may represent an essential programming process. In boys, long-term testicular hormonal function and spermatogenesis seem to be, at least in part, regulated by minipuberty. On the contrary, the role of minipuberty in girls is still uncertain. Recently, androgen exposure during minipuberty has been correlated with later sex-typed behavior. Premature and/or SGA infants show significant differences in postnatal HPG axis activity in comparison to full-term infants and the consequences of these differences on later health and disease require further research. The sex-dimorphic HPG activation during mid-gestation is probably responsible for the body composition differences observed ad birth between boys and girls, with boys showing greater total body mass and lean mass, and a lower proportion of fat mass. Testosterone exposure during minipuberty further contributes to these differences and seems to be responsible for the significantly higher growth velocity observed in male infants. Lastly, minipuberty is a valuable “window of opportunity” for differential diagnosis of disorders of sex development and it represents the only time window before puberty when congenital hypogonadism can be diagnosed by the simple analysis of basal gonadotropin and gonadal hormone levels.